In situ measurements of NO, NO2, NOy, and O3 in Dinghushan (112°E, 23°N), China during autumn 2008 - Sun, Yang; Wang, Lili; Wang, Yuesi; Zhang, Deqiang; Quan, Liu; Jinyuan, Xin (Atmospheric environment (1994), 2010)
Measurements of O3, NO, NO2, and NOy mixing ratios were carried out at a station-Dinghushan in Guangdong province of China from Oct. 18th, 2008 to Nov. 7th, 2008. This research shows that under conditions of a strong subtropical high (temperature high, relative humidity low), on Oct. 29th, 2008 the Dinghushan station observed severe photochemical pollution. The Maximum hour average concentration of O3 reached 128aappbv, and the serious photochemical pollution is caused by superposition of local photochemical reaction and regional transport. The observation that NOx ozone production efficiency (OPE) values for high O3 pollution on Oct. 29-30th, 2008 were 10.5 and 15, which were more than the values of the city source region and lower than that of the surrounding clean areas. It means the sensitivity of O3 generated was transitioning from VOCs limited condition to NOx-limited regime. By applying a Smog Production Model, the results show that the extent of reaction values less than 0.6 were occurred on 17 days during campaign, and 13 days for the extents of reactions more than 0.6. However, there were no data with values over 0.8, which indicates that the observation station represent a VOCs sensitive system during campaign. Analysis of the extents of reactions and wind data show that the pollution is mostly subject to a southeasterly airflow influence.